Agathilla bohartorum Wahl, 1985 (Hymenoptera: Ichneumonidae: Banchinae) colectada sobre Bidens pilosa L. (Asteraceae) - Ruiz-Cancino, Enrique; Coronado-Blanco, Juana María; Lomelí-Flores, José Refugio (Instituto de Ecología, A.C., 2015)
Agathilla Westwood is an endemic genus of the family Ichneumonidae in North America, with three species from the United States of America and two from Mexico (A. fulvopicta Westwood in Belén Barranca -no state name in label- and Durango; A. bohartorum Wahl in Durango, Estado de México, Jalisco and Zacatecas). This is the first record of A. bohartorum collected on Bidens pilosa Linnaeus (Asteraceae).